Shiga Toxin-Producing Escherichia coli (STEC) in Developing Countries: A 10-Year Review with Global Perspective - Nemati, Ali; Dadvar, Ali; Eppinger, Mark; Karimpour, Zohreh; Saberi Kakhki, Soroush; Sabeti Moghaddam Sabzevar, Alireza; Badouei, Mahdi Askari; Gigliucci, Federica; Santos, Luis Fernando dos; Nakamura, Keiji; Javidi, Hooman; Hafiz, Maryam (Microorganisms (Basel), 2025)
In the past two decades, Shiga toxin-producing Escherichia coli (STEC) has been responsible for multiple large-scale outbreaks worldwide, affecting thousands of individuals. While surveillance systems in developed countries such as the United States, the United Kingdom, Europe, Australia, Japan, and Canada are well-established, data on STEC prevalence in developing nations remain sparse, partly due to the absence of well-structured molecular diagnostic networks or surveillance systems. This review analyzed 250 studies published between 2014 and 2024 across 39 developing countries in Africa, Asia, Latin America, and the Caribbean, yielding 8986 STEC isolates. Detailed serogroup and serotype data were available for 55.9% of these, with O111, O157, and O26 being most common in humans. In animals, O157:H7 was most frequent, while food isolates mirrored global trends with O157 and O111 dominance. Notably, O145, a serogroup frequently reported in the U.S. and Europe, was absent from the ‘’Top Seven’’ serogroups. Shiga toxin subtypes stx1a and stx2a were most prevalent in human cases. In animal isolates, stx2e was the most prevalent subtype, while stx2c was most commonly found in food samples. We recommend establishing reference laboratories in these regions to improve data quality, strengthen monitoring efforts, and reduce the burden of STEC infections globally.